THE INFLUENCE OF GENERAL ALLOCATION FUNDS, SPECIAL ALLOCATION FUNDS AND CAPITAL EXPENDITURE ON ECONOMIC GROWTH IN ACEH PROVINCE IN 2010-2021 - Putra, Agung Mustopa; Usman, Umaruddin (LPPM Universitas Malikussaleh, 2024)
This study aims to determine the effect of general allocation funds, special allocation funds, and capital expenditures on economic growth in Aceh Province in 2010-2021. The variables in this study are economic growth as the dependent variable and general allocation funds, special allocation funds and capital expenditures as independent variable. Updates from this research on previous research are the variables studied, namely economic growth, general allocation funds, special allocation funds and capital expenditures, the research year is 2010-2021 and the object of research is the Province of Aceh. The data used in this study are data obtained from the Badan Pusat Statistik for 23 districts/cities of Aceh Province. The analitycal method used in multiple linear regression with the ordinary least square (OLS) method. This study uses classical assumption tests such as the normallyty test, multicolinearity test, autocorrelation test, and heteroscedaticity test. The regression tool in this study used Eviews 10 software. The result of the analysis show that general allocation funds and special allocatrion funds have a positive and significant effect on economic growth, while capital expenditure has a negative and significant on economic growth.